Optical Properties of Cancrinite - Kylänpää, Tinja (My University, 2026)
Cancrinite (Na₈Al₆Si₆O₂₄(OH)₂∙H₂O) is an aluminosilicate mineral with an ordered framework of 6- and 12-memebered rings which form a porous network structure. These pores can host e.g. CO₃²⁻, OH⁻, Cl⁻, SO₄²⁻ anions and K⁺, Ca²⁺, Cs⁺ cations which can cause optical properties in cancrinite. The most common route for cancrinite preparation is hydrothermal synthesis using Teflon-lined steel-autoclaves in alkaline media to create the needed dissolution for crystallisation. The synthesis has been optimised for several different applications, some of which include pigment development, radioactive waste management, and photonic crystals. Cancrinite readily accepts several different ions, but the recent studies have focused more on the naturally occurring cancrinite or entrapment of radioactive ions. Most properties of cancrinite are still uncovered, since the research on it has been scarce. This thesis aims to explore the photochromic and luminescent properties of cancrinite. In this research, cancrinite samples with various anions and cations were synthesised. Each sample batch, named by their cation(s), were characterised by powder X-ray diffraction, X-ray fluorescence spectroscopy, as well as diffuse reflectance and photoluminescence spectroscopies. Additionally, field emission scanning electron microscopy combined with energy-dispersive X-ray spectroscopy, thermoluminescence, and optically stimulated luminescence measurements were carried out of the samples that excelled in their properties. Depending on the results of thermoluminescence and optically stimulated luminescence, possible dental X-ray image could be obtained. The results showed that cancrinite readily accepted ions creating colour and luminescence centres with certain samples showing better properties. While the properties of cancrinite are not comparable to the properties of sodalites, these properties reveal more about the mechanisms of cancrinite-group minerals.
Keywords: cancrinite; ion substitution; photochromism; luminescence